Comparison of influenza type A and B with COVID‐19: A global systematic review and meta‐analysis on clinical, laboratory and radiographic findings. (9th October 2020) - Pormohammad, Ali; Ghorbani, Saied; Khatami, Alireza; Razizadeh, Mohammad Hossein; Alborzi, Ehsan; Zarei, Mohammad; Idrovo, Juan‐Pablo; Turner, Raymond J.
Summary: We compared clinical symptoms, laboratory findings, radiographic signs and outcomes of COVID‐19 and influenza to identify unique features. Depending on the heterogeneity test, we used either random or fixed‐effect models to analyse the appropriateness of the pooled results. Overall, 540 articles included in this study; 75, 164 cases of COVID‐19 (157 studies), 113, 818 influenza type A (251 studies) and 9266 influenza type B patients (47 studies) were included. Runny nose, dyspnoea, sore throat and rhinorrhoea were less frequent symptoms in COVID‐19 cases (14%, 15%, 11.5% and 9.5%, respectively) in comparison to influenza type A (70%, 45.5%, 49% and 44.5%, respectively) and type B (74%, 33%, 38% and 49%, respectively). Most of the patients with COVID‐19 had abnormal chest radiology (84%, p < 0.001) in comparison to influenza type A (57%, p < 0.001) and B (33%, p < 0.001). The incubation period in COVID‐19 (6.4 days estimated) was longer than influenza type A (3.4 days). Likewise, the duration of hospitalization in COVID‐19 patients (14 days) was longer than influenza type A (6.5 days) and influenza type B (6.7 days). Case fatality rate of hospitalized patients in COVID‐19 (6.5%, p < 0.001), influenza type A (6%, p < 0.001) and influenza type B was 3%( p < 0.001). The results showed that COVID‐19 and influenza had many differences in clinical manifestations and radiographic findings. Due to the lack of effective medication or vaccine for COVID‐19, timely detection of this viral infection and distinguishing from influenza are very important.